Interactional fairness as a mediator between merit-based pay management and organizational commitment / Mohd Ridwan Abd Razak and Enah Ali - Abd Razak, Mohd Ridwan; Ali, Enah (Accounting Research Institute (ARI), UiTM Shah Alam, 2021)
The purpose of this quantitative study was to evaluate the ability of interactional fairness as a mediator in the relationship between merit-based pay management (such as communication and performance assessment) and organizational commitment. A cross-sectional technique was used to collect 450 useable data of workers from a government-linked company (GLC), who had served more than five years in Selangor and Kuala Lumpur. The outcomes of the Partial Least Square Structural Equation Modelling (PLS-SEM) path model analysis indicated three important findings. First, communication and performance assessment was significantly correlated with interactional fairness. Second, interactional fairness was significantly correlated with organizational commitment. Third, communication, performance assessment and interactional fairness were significantly correlated with organizational commitment. Statistically, the findings of this study verified that the relationship between communication and performance assessment with organizational commitment is indirectly influenced by interactional fairness. These findings would benefit researchers and organizational management to recognize the importance of merit-based pay management (communication and performance assessment) to nurture employees' positive feelings, behaviors, and attitudes in an organization. An effective pay management system would likely improve employees' morale and enhance organizational competitiveness in facing the challenges of the COVID-19 pandemic.